Effect Of The Combination Of "Master Herbs" As A Complementary Effort To Improve Sleep Quality For Postpartum Mothers - Anggraini, Ryzky Diah; Ariestantia, Dwi Riyan; Lovita, Bebi; Feridiana, Vernanda (Bunda Edu-Midwifery Journal (BEMJ), 2023)
During the postpartum period, the fulfillment of the need for rest and sleep is very much needed and this has an important role for the mother in the process of breastfeeding and health recovery after pregnancy and childbirth. Postpartum mothers often experience a decrease in sleep quality. Complementary services are a safe choice and have minimal side effects. Master Herbs is a combination of massage aromatherapy and herbal steambath which can improve the sleep quality of postpartum mothers. This research is a type of Quasi Experiment research with a Pre test and Post Test Control Group research design. The results of this study were that there was a significant effect pvalue 0.001 Master Herbs pvalue on sleep quality. Providing a combination of aromatherapy massage and herbal steambath as a complementary effort in midwifery can be applied to improve sleep quality for postpartum mothers